(untitled) (The International Journal for Scientific Research, 2024)
Islamic law emphasizes the prohibition of killing women in the context of wars and conflicts, highlighting the commitment to principles of mercy and justice, even during combat. The teachings of Prophet Muhammad (peace be upon him) explicitly instruct against targeting vulnerable groups, underlining the fundamental value of civilian protection. Moreover, Islamic teachings stress the importance of respecting individual dignity and the bonds of family, prohibiting any actions that harm or demean. Pregnant women are afforded special compassion, with scholars asserting that they should not face the death penalty, which reflects the depth of mercy inherent in Islamic teachings and the commitment to protecting life. To address these issues, the following recommendations are proposed: reaffirming the prohibition of killing women in conflicts, raising awareness about the respect for individual dignity, particularly the protection of pregnant women, and promoting the safeguarding of civilians. Scholars should continue advocating against the killing of non-combatants while ensuring protection measures for women in warfare are respected. Finally, emphasizing values of mercy and justice within the community is essential to uphold the dignity of families and protect women, especially during crises.